The shock of the SARS-CoV-2 pandemic on health professionals’ education: A pilot qualitative study in Malaysia - Krishnapillai, Ambigga; Lugova, Halyna; Haque, Mainul; Suthahar, Ariaratnam; Abdul Aziz, Aznida Firzah; Hasan Maziz, Mohammad Nazmul; Shridhar Patil, Sapna; Daher, Aqil M; Muhammad Ali, Suhaila; A. Rahman, Nor Azlina; A Rahman, Nor Iza; Chowdhury, Kona; et al. (2022)
Various measures were introduced globally to prevent the spread of COVID-19, including travel restrictions, social distancing, and closure of educational establishments. Implementing these measures resulted in appreciable changes to health professions’ education (HPE) with concerns regarding the level of preparedness among faculty members and students towards e-learning, including laboratory, clinical, and other forms of hands-on training. In addition, the affordability of devices and Internet bundles arose, especially among students in low- and middle-income countries. A pilot qualitative study was conducted in Malaysia to ascertain critical challenges and how higher learning establishments addressed them. The study was undertaken among 10 purposely selected educators in both public and private universities in Malaysia using an established questionnaire to ascertain critical challenges and responses. The main issues included unfamiliarity with e-learning approaches and inadequate availability of devices and Internet bundles among students. Furthermore, the study revealed a lack of interaction between faculty members and students, concerns with conducting practicals and clinical examinations, and mental distress among faculty members. Measures introduced to address concerns included supporting digital needs through the provision of software, devices, and Internet bundles, enhanced training of educators in e-learning approaches, providing clinical case banks and curated patient data, and establishing clear policies and procedures for classroom and clinical teaching. Psychological support, including stress management, was also provided. The challenges and lessons learned in Malaysia regarding HPE during the pandemic were similar to other countries with hybrid learning here to stay.